2019
DOI: 10.1016/j.eurox.2019.100061
|View full text |Cite
|
Sign up to set email alerts
|

The association among cervical, anal, and oral HPV infections in high-risk and low-risk women

Abstract: Objective The human papillomavirus (HPV) can cause premalignant and malignant tumors in the anogenital and oropharyngeal regions. The aim of this study was to describe the association in the prevalence of cervical, anal, and oral HPV infections in high-risk patients with biopsy-confirmed high-grade cervical lesion compared to low-risk women. Study Design A total of 718 immunocompetent women were enrolled in the study. The high-risk (HR) group consisted of 473 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 17 publications
2
25
0
1
Order By: Relevance
“…Our findings have also shown that the prevalence of HPV infection is more common in the anus (78.4%) than in the penis (36.2%), oral cavity (17.3%) and urethra (15.4%). These results confirm the hypothesis that the anatomic site of infection can influence the natural history of HPV 151–153 . There are several possible factors that may contribute to the observed differences in incidence, and these include a greater tendency for epithelial microtrauma in the anal canal, differences in local mucosal immunity like the continuous secretion of saliva and associated antibodies into the oral cavity and differences in the frequency of sexual behaviours related to transmission.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings have also shown that the prevalence of HPV infection is more common in the anus (78.4%) than in the penis (36.2%), oral cavity (17.3%) and urethra (15.4%). These results confirm the hypothesis that the anatomic site of infection can influence the natural history of HPV 151–153 . There are several possible factors that may contribute to the observed differences in incidence, and these include a greater tendency for epithelial microtrauma in the anal canal, differences in local mucosal immunity like the continuous secretion of saliva and associated antibodies into the oral cavity and differences in the frequency of sexual behaviours related to transmission.…”
Section: Discussionsupporting
confidence: 82%
“…The prevalence of HPV in our study population was relatively high, which is likely due to the increased exposure to HPV in sexual health center visitors. Similar to previous studies, hrHPV types were more prevalent than lrHPV types [ 19 , 20 ]. We also found that the prevalence of concurrent genital-anal HPV infections with nearly all HPV types was higher than could be expected by chance.…”
Section: Discussionsupporting
confidence: 89%
“…Multiple studies have suggested alternative non-sexual routes of transmission, which include contact between the anogenital site and the fingers, mouth or other skin contact [ 22 ]. Self-inoculation or partner-assisted inoculation have also been described as a potential route of HPV transmission [ 23 ], in which the cervix is proposed as the main source for HPV infection in the anus [ 20 ]. Accordingly, a higher risk for cervical-to-anal HPV infection compared to anal-to-cervical HPV infection was reported with respective hazard ratios of 14.2 (95% CI = 9.86–20.05) and 7.08 (95% CI = 3.94–12.7).…”
Section: Discussionmentioning
confidence: 99%
“…In other studies comparing groups of women with and without genital SILs, there were differences in the smoking status, number of sexual partners, and history of anal intercourse in these groups, with anal intercourse being more frequent in women with genital SILs. 5,[16][17][18] These factors alone may increase the presence of anal Hr-HPV, abnormal anal cytology, and anal SILs. 3,4,10,19 The occurrence of abnormal anal cytology was more frequent in women with genital SILs than in those without SILs; however, this difference may not be significant because all women included in the genital SIL group had an ongoing histopathological diagnosis of a genital SIL, not just a past medical history of genital SILs, which limited the sample.…”
Section: Discussionmentioning
confidence: 99%